(untitled) (Indian Journal of Biochemistry and Biophysics (IJBB), 2023)
Conjugated linoleic acid (CLA) is a polyunsaturated fatty acid with various positional and geometric isomers of linoleic acid (LA) present mainly in food items and produced endogenously in non-ruminants and humans or through fermentation process. It is associated with health-beneficial effects and subject to more research on its natural sources (ruminant-derived foods) and strategies to increase the content in various foodstuffs. Although several studies have reported the most common intake value of 0.8 g/day (0.6 to 3.0 g/day), research for raising in situ concentration should focus on strategies such as in vitro bioconversion of its precursors by bacteria and supplementation of LA rich-oils in foods fermentation process. In this study, the ability of some lactic acid bacteria (LAB) from diverse samples to produce CLA from sunflower oil and the effect on production yield of fermentation medium supplementation with carbonate calcium were investigated. Results showed that ten Limosilactobacillus fermentum and Enterococcus faecium produced trans-10, cis-12-CLA isomer accounted for at least 85% of total CLA ranging from 4.64 to 5.22 µg/mL. Despite the fermentation medium supplementation with CaCO3 enhanced the production yield, the residual LA inhibitory effect on bacteria growth governing CLA biosynthesis process was not mitigated. So, although our LAB strains can produce CLA, the more the LA concentration goes up, the more the conversion rate downgrades. Further studies on strains behavior in a wide range of LA concentrations will help establish a stable relationship between bacteria and LA in the presence of CaCO3.